2021
DOI: 10.18632/aging.203013
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circRNA 0001445 promotes glioma progression through miRNA-127-5p/SNX5 pathway

Abstract: Background: Glioma is one of the most wide-spreading brain cancers worldwide. Exosomes have emerged as essential regulators in intercellular communication, and exosomal circular RNAs (circRNAs) are critical for cancer progression. In this study, we aimed to investigate the role of exosomal circRNAs in glioma progression and associated mechanisms. Methods: Exosomes derived from glioma cells were isolated and identified by transmission electron microscopy and nanoparticle tracking analysis (NTA). CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Past studies indicated that circRNAs could be packaged into exosomes and play an important role in the progression of tumours [ 38 , 39 ]. Then, to investigate whether circNEIL3 can be loaded into exosomes, we collected exosomes from the supernatants of cultured GBM cells, which exhibited similar typical cup-shaped morphology, size, and number (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Past studies indicated that circRNAs could be packaged into exosomes and play an important role in the progression of tumours [ 38 , 39 ]. Then, to investigate whether circNEIL3 can be loaded into exosomes, we collected exosomes from the supernatants of cultured GBM cells, which exhibited similar typical cup-shaped morphology, size, and number (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionaly, tumor-released exosomal circ-PDE8A absorbed miR-338 to regulate metastasis associated in colon cancer 1 and promoted the invasive growth of pancreatic ductal adenocarcinoma cells via the metastasis associated in colon cancer /MET/extracellular regulated protein kinases or protein kinase B pathways [ 12 ]. Further, exosomal circRNA 0001445 servered as a sponge for miRNA-127-5p to increase sorting nexin 5 expression and then facilitate the progression of glioma [ 13 ]. Notably, using high-throughput sequencing, Yang et al [ 14 ] found that exosomes extracted from the sera of PTC patients displayed upregulated hsa_circ_007293 (circ007293) expression.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism provides a new explanation for arsenite-induced cancer. Glioma-derived exosomal circRNA-0001445 ( Han et al, 2021 ) significantly promotes proliferation and inhibits the apoptosis of glioma cells via the miRNA-1275p/SNX5 signaling pathway. Shi et al ( Xiao and Shi, 2020 ) found that exosomal circRNA_400068 produced by renal cell carcinoma cells promotes the proliferation of healthy kidney cells, significantly inhibits their apoptosis, and promotes their transformation to malignancy, which may be due to signaling through regulation of the miRNA-210-5p/SocS1 axis pathway.…”
Section: Biological Characteristics Of Exosomal Circrnasmentioning
confidence: 99%